Expanding a Foot Care Education Program for Nurses: A Quality Improvement Survey. Issue 5 (September 2019) - Beuscher, Tara L.; Moe, Hollie L.; Stolder, Mary Ellen; Peloquin, Lois; Nesbitt, Bonnie
Abstract : Faculty of a foot care continuing education program in the Midwest sought to determine current practice and interest in expanding the current program, both didactic and clinical, to meet expanded requirements in certification criteria. An electronic e-mail survey with both quantitative and qualitative questions was developed and sent to 445 past participants who completed the Foot and Nail Care: Education for Nurses Program hosted by the University of Wisconsin–Eau Claire Continuing Education over the past 5 years. There were 99 responses for a response rate of 22%. We asked several questions about clinical practice specific to the use of equipment, roles and responsibilities, and practice sites. Most participants used a mechanical rotary file for debriding toenails in their practices, with almost half having obtained a more advanced rotary file the longer they practiced. Most participants practiced in a variety of roles and settings including part of their paid employment, an independent business (full- or part-time), or volunteer. Less than half of respondents have become certified in the specialty. Those who have sought certification have chosen either the Wound Ostomy Continence Nursing Certification Board's Certified Foot Care Nurse or the American Foot Care Nurses Association's Certified Foot Care Specialist (CFCS). Sufficient interest (77%; n = 75) was expressed to expand the course to meet the requirements of certification, specifically for clinical hours. Based on the results of this survey, we concluded there is value in offering the program with several modules where participants could complete an introductory course and have the option to participate in continued education should they decide to learn more, seek certification, or need continuing education for recertification.